A Critical Comparison between First- and Second-Generation Cryoballoon for Paroxysmal Atrial Fibrillation Ablation - Sergio Conti; Claudio Tondo (Current Topics in Medicine and Medical Research Vol. 13, 2021)
Introduction: Cryoballoon (CB) ablation has emerged as a novel treatment for pulmonary vein isolation (PVI) for patients with paroxysmal atrial fibrillation (PAF). Cryoballoon (CB) technology would theoretically allow PVI with a single application the second-generation Arctic Front Advance (ADV) was redesigned with technical modifications aiming at procedural and outcome improvements. We aimed to compare the efficacy of the two different technologies over a long-term follow-up. Methods: A total of 120 patients with PAF were enrolled. Sixty patients underwent PVI using the first- generation CB and 60 patients with the ADV catheter. All patients were evaluated over a follow-up period of 2 years. Results: There were no significant differences between the two groups of patients. Procedures performed with the first-generation CB showed longer fluoroscopy time (36.3 ± 16.8 versus 14.2 ± 13.5 min, resp.; ???? = 0.00016) and longer procedure times as well (153.1 ± 32 versus 102±24.8 min, resp.; ???? = 0.019). The overall long-term success was significantly different between the two groups (68.3 versus 86.7%, resp.; ???? = 0.017). No differences were found in the lesion areas of left and right PV between the two groups (resp., ???? = 0.61 and 0.57). There were no significant differences in procedural-related complications. Conclusion: The ADV catheter compared to the first-generation balloon allows obtaining a significantly higher success rate after a single PVI procedure during the long-term follow-up. Fluoroscopy and procedural times were significantly shortened using the ADV catheter. Based on electroanatomical mapping, lesion areas created by the two CB were not statistically different.